Sinonim dan Antonim dalam Al-Qur'an - Ridlo, Ubaid (Universitas Islam Negeri Raden Intan Lampung, 2017)
Abstract: This article explains the various things about synonyms and antonyms in Arabic linguistic studies. Readers are invited to discuss cross-references on the definition of synonyms and antonyms in the Arabic linguistic context, the background of the emergence of synonyms and antonyms in Arabic, the variety of synonyms and antonyms, and the phenomenon of synonyms and antonyms in the Qur'an. Differences in understanding synonyms and antonyms result in differences in interpreting the Qur'an. Mainstream there are two kinds of pro synonyms and antonyms and counter synonyms and antonyms in the Qur